Emergency Medicine An International Perspective - Blaivas, Michael (IntechOpen, 2012)
Emergency Medicine is an expanding field that has spread beyond the shores of North America and has taken on different characteristics around the world. Although many of the struggles of emergency practitioners are similar, the field and its principles have adapted to local needs and resources. This book seeks to educate readers not only on emergency medicine theory, science and practice, but also reflects that multinational nature of emergency medicine, allowing readers to learn from experiences of others. This diverse group of authors presents a true international view of emergency medicine practice and science that will be educational for any reader.